Selective Susceptibility of Oligodendrocytes to Carbon Monoxide Poisoning: Implication for Delayed Neurologic Sequelae (DNS) - Tian, Xiaofei; Guan, Teng; Guo, Ying; Zhang, Guohui; Kong, Jiming (Frontiers in Psychiatry, 2020)
Delayed neurologic sequelae (DNS) are recurrent–transient neuropsychiatric consequences of carbon monoxide (CO) intoxication. Pathologically DNS features damages to the brain white matter. Here we test a hypothesis that direct cytotoxicity of CO to oligodendrocytes plays a role in the development of DNS. In an in vitro model of CO poisoning with the carbon monoxide releasing molecule-2 (CORM-2) as a CO donor, we show that CORM-2 at concentrations higher than 200 M significantly inhibited viability and caused significant death of PC12 cells. Similar minimum toxicity concentration was observed on primary brain cells including neurons, astrocytes and microglia. Interestingly, oligodendrocytes showed cytotoxicity to CORM-2 at a much lower concentration (100 micromoles). We further found that CORM-2 at 100 micromoles inhibited proteolipid protein (PLP), PLP production and reduced myelin coverage on axons in an in vitro model of myelination. Our results show support that direct cytotoxicity is a mechanism of CO poisoning and DNS may result from a high vulnerability susceptibility of oligodendrocytes to CO poisoning.